Rural Non-Agricultural Employment in Kerala : Inter-District Variations - Mridul Eapen (Economic and Political Weekly March 25, 1995, 1995)
This paper focuses on changes between 1971 and 1991 in inter-district variations in rural non-agricultural employment in Kerala. The determinants of non-agricultural employment are examined through correlation analysis